Age and Ageing During the COVID-19 Pandemic; Challenges to Public Health and to the Health of the Public - Clarfield, A. Mark; Dwolatzky, Tzvi (Frontiers in Public Health, 2021)
The distribution of the SARS-CoV-2 virus has reached pandemic proportions. While COVID-19 can affect anyone, it is particularly hazardous for those with "co-morbidities" such as obesity, ischemic heart disease, hypertension, etc. Older age (55+) is an especially strong and independent risk factor for hospital and ICU admission, mechanical ventilation and death. Health systems must find ways to protect all persons at any age but with particular attention to those with risk factors. However, essential freedoms must be protected, and the social/psychological needs met for those shielded. The example of the older population in Israel at the time of COVID-19 may have interesting public health lessons. Relatively speaking, Israel is a demographically young country, with only 11.5% of its population 65 years and older as compared with the OECD average of >17%. As well, a lower proportion of older persons are in long-term institutions in Israel than in most other OECD countries. These characteristics, together with the initiation of a national program to protect older residents of nursing homes, may account for the relatively low rates of serious disease and mortality in Israel. However, the situation remains unstable and the situation for older persons could quickly deteriorate anywhere. The rollout of efficacious vaccines is in progress but will take years to cover the world's population. Every effort must be made not to leave poorer countries behind. Marrying the principles of public health (care of the population) with those of geriatric medicine (care of the older individual) offers the best way forward.